VD_FINDINFO Décision / 2014 / 1027 vom 20. November 2014 - VD Tribunal cantonal (2014)
SUSPENSION DE LA PROCÉDURE, CONDUITE DU PROCÈS, ENQUÊTE PÉNALE | 314 al. 1 let. a CPP (CH), 314 al. 3 CPP (CH), 5 CPP (CH)